(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: The gastroenterologists along with histopathologists are carrying out early diagnosis and surveillance of patients presenting with ulcerative colitis. A long term treatment and follow up by a gastrointestinal unit is needed in diagnosed cases of ulcerative colitis. As a part of quality assurance, this audit was done to analyze the consistency of diagnosis of ulcerative colitis on non-neoplastic colorectal biopsies and to compare audited results with originally diagnosed reports in cases of ulcerative colitis. Material and Methods: The study was conducted in Histopathology department of Shaikh Zayed Hospital Lahore Pakistan. H & E stained slides of 500 diagnosed cases of ulcerative colitis were retrieved from the record in time period between February 2012 to June 2013. The cases were reviewed for three histological parameters i.e., architecture of epithelium, chronic and acute inflammation. The new observations were recorded in a specially designed proforma and compared with original reports. Results: A definite diagnosis of ulcerative colitis in our study was proved correct in 100% of cases. Where the biopsy which was reported as suggestive of ulcerative colitis, 97.9% proved to have ulcerative colitis. Conclusion: This audit concluded that diagnosis of colorectal biopsies with high suspicion of ulcerative colitis should be carried out on a proforma which clearly depicts all the relevant histological features that may be important to the histopathologists for diagnosis and to the gastroenterologist for clinical treatment. The clinical findings given by the physician was another area of improvement.